SUGGESTED VISUALIZATION FOR SOME QUALITY ELEMENTS OF EXTENSION SERVICE FOR VEGETABLE FARMERS FROM THEIR VIEWPOINT IN THE GOVERNORATE OF BAGHDAD - Al-Hafidh , Fatima S.; Al-Taiy, H.K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study objective was aimed to prepare a suggested conception for the quality of some elements of the extension service for vegetable growers from their point view at Baghdad Governorate. In order to achieve the objective , a scheme was prepared consisting of (20) criteria distributed into (4) areas: sources of service provision, service timing, topics and content of the extension services, service providers. Data were collected by the random sample of 108 respondents vegetable growers, representing 30% of the agricultural divisions. In the two directorates of agriculture in Baghdad Governorate , Al-Karkh , Al-Rusafa. The results of this research concluded that each of the areas and criteria of the proposed perception obtained a weighted average located between 3.01 and 3.34, which is greater than the hypothetical mean of 2.5 degrees, and the survival of all areas and criteria mentioned above in their final form. Accordingly, the researchers recommend that the Agricultural Extension and Training Department adopt what came in this study.